A Rose by any Other Name: Systematics and Diversity in the Chilean Giant Barnacle Austromegabalanus Psittacus () (Cirripedia). Issue 2 (1st March 2016) - Pappalardo, Paula; Pitombo, Fabio B.; Haye, Pilar A.; Wares, John P.
Abstract: We analyzed the population structure of the edible barnacle Austromegabalanus psittacus (Molina, 1782 ) along most of the coast of Chile. The analysis of population structure was based on nucleotide sequences of the mitochondrial cytochrome oxidase I (COI) gene region. We also tested for differences between the regions to the north and south of $30 - 33^° {\rm{S}}$, as these latitudes represent a recognized biogeographic break and important oceanographic transitions occur in that area. No geographic differentiation was evident when using Hudson's nearest-neighbor ${(S_{\rm{nn}}})$ statistic to analyze genetic differences between all populations. ${F_{\rm{st}}}$ values nevertheless showed overall genetic structure among sites. Significant geographic structure was found using ${S_{\rm{nn}}}$ and analysis of molecular variance (AMOVA) when locations were separated into northern and southern regions, with a stronger signal when the geographic division is set at $33^° {\rm{S}}$ . Our results support the idea that oceanographic transitions can affect the genetic structure in species with pelagic larvae. We also discuss observations on size structure differences within the natural range of A. psittacus and this barnacle's sympatric occurrence with another barnacle, Megabalanus concinnus (Darwin, 1854 ) in its northern range.